Convocation 2003 (Institutional Knowledge at Singapore Management University, 2003)
Guest of honour, Dr Victor Fung, Chairman of Li & Fung Group and SMU trustee, speaking at Singapore Management University's Convocation 2003. Photo taken on 16 August 2003.